Penguatan Penyampaian Laporan SPT Tahunan PPh Pasal 21 Dengan E-SPT Wajib Pajak Orang Pribadi Bagi Pegawai Kantor Kecamatan Arcamanik Bandung - Bramasto, Ari; Astuti, Ayi; Saepudin, Asep; Ockativian, Rizky Ferari (Jurnal Pengabdian Tri Bhakti, 2019)
On-line Annual Tax Returns Article 21 Taxpayers Socialization of 2018 Personal Taxpayers using e-SPT on March 2019 can increase knowledge for citizens about 21 annual income tax reporting, especially in the Lengkong District environment and from the socialization it increases tax reporting knowledge income as provisions for the citizens of the Arcamanik District of Bandung and can follow the current tax developments.